Pure metals for creation the nuclear structural materials - Pylypenko, Mykola Mykolayovych; Yefimov, Oleksandr Vyacheslavovych; Potanina, Tetiana Volodymyrivna (ProQuest LLC, 2024)
The paper presents the main results of research on the development of structural materials for equipment elements of existing and prospective nuclear power plants. The further development of nuclear energy largely depends on the development of advanced structural materials for new generation reactors and the improvement of materials for operating nuclear power plants. The high requirements for structural materials regarding the content of impurity elements can be met only when high-purity metals are used as initial components and new technologies for their production are used. The prospects of using new methods and approaches for evaluating and improving the physico-mechanical and physico-chemical properties (microhardness, corrosion resistance, radiation resistance, etc.) of structural materials for nuclear technologies were considered.
Keywords: pure metals; refining process; properties; structural materials; alloys; interval and regression analysis